기록물 평가정책 수립 관점에서 본 국가기록원 소장 기록물 분석 - 오현진; 윤은하; Hyun-Jin Oh; Eunha Youn (Journal of Records Management & Archives Society of Korea, 2025)
This study aims to analyze the suitability of the records held by the National Archives of Korea with the permanent preservation standards outlined in Appendix 1 of the Enforcement Decree of the Public Records Management Act. It seeks to identify the current status and issues, providing the implications necessary for establishing a national records appraisal policy. The study classifies the permanent records held by the National Archives of Korea into three categories: documenting government activities, providing evidence for citizens' rights, and recording national experiences. Through this analysis, several cases where the standards prescribed by the law and the guidelines for retention periods differed were identified. Furthermore, matching the records inventory with Appendix 1 revealed that records related to providing evidence for citizens' rights were most frequently identified, while those related to recording national experiences were the least identified. Ultimately, this study highlights the need for specific and practical appraisal criteria and policy frameworks through the analysis of actual records holdings, emphasizing the necessity of establishing appraisal and selection standards to ensure objectivity and consistency in records appraisal. 이 연구는 우리나라 국가기록원이 보유한 기록물과 공공기록물법 시행령 별표1의 영구 보존 기준의 적합성을 분석하고, 현황과 문제점을 도출하여 국가기록물 선별정책 수립에 필요한 시사점의 제공을 목적으로 한다. 국가기록원이 소장한 영구 기록물을 정부활동의 기록화, 시민의 권리 증빙, 국가적 경험의 기록화라는 세 가지 범주로 분류하여 분석하였으며, 이를 통해 법령에서 정한 기준과 보존기간 준칙이 다른 경우를 다수 확인 할 수 있었다. 기록물철 목록과 별표1 매칭 결과 시민의 권리 증빙과 관련된 기록물이 가장 많이 식별되었으며 국가적 경험의 기록화 해당 기록물이 가장 적게 식별되었다. 본 연구는 실제 보유기록물 분석을 통해 구체적이고 실효성 있는 기록물 평가 기준과 정책문의 필요성을 제안한다. 기록물 평가 및 선별기준 수립을 통해 기록물 평가의 객관성과 일관성을 확보할 필요가 있음을 강조한다.